Between amateurism and science: Caterina Pigorini Beri’s proto-ethnography in Costumi e superstizioni dell’Appennino marchigiano (Altre Modernità, 2023)
The work Costumi e superstizioni dell’Appennino marchigiano by Caterina Pigorini Beri is not only a document of precious archival and historical importance on the uses of the Marche hinterland of the late nineteenth century, but also opens a window for reflection on two other important issues: the first is the condition of the intellectual woman who, in the absence of specific training, conducts her research in an autonomous and pioneering manner. The work highlights an emerging contrast between amateurism, linked to the sphere of the feminine, and science, the field of male domination. Since Pigorini Beri's work is independent of a specific discipline and a scientifically structured working method, it is placed in a crossroad between the travel notebook, the impressionistic sketch, and the ethno-anthropological description. However, the insights contained in the work (see the meaning of "paganity" attributed to local folkloristic manifestations), the work of gathering information, the posture of the author (inside and outside the narrated world), introduce at a primitive and developing level those elements of methodology that will characterize De Martino's ethnographic and anthropological study in the twentieth century.The second question concerns the overall meaning that the author entrusts to her story, in controversy with the "intrusive positivism" of the era she is living. From this perspective the work seems to have its reasons rooted in the "anti-modernist" positions of the late nineteenth century, where saving the culture of local realities from oblivion is not only an operation of intellectual value, but a necessary condition for acquiring knowledge of the world.
Keywords: women; amateurism; literature; science; ethno-anthropology; folklore